A Realistic Model of Human Structure from the Visible Human Data - Höhne, K. H.; Pflesser, B.; Pommert, A.; Riemer, M.; Schubert, R.; Schiemann, T.; Tiede, U.; Schumacher, U. (Methods of Information in Medicine, 2001)
The computer-based 3D models of the human body reported to date suffer from poor spatial resolution. The Visible Human project has delivered high resolution cross-sectional images that are suited for generation of high-quality models. Yet none of the 3D models described to date reflect the quality of the original images. We present a method of segmentation and visualization which provides a new quality of realism and detail. Using the example of a 3D model of the inner organs, we demonstrate that such models, especially when combined with a knowledge base, open new possibilities for scientific, educational, and clinical work.
Keywords: 3D-visualization; Anatomy; Atlas; Visible Human; Ontology